2005
DOI: 10.2993/0278-0771(2005)25[59:fbcomm]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Folk Biological Classification of Minor Millet Species in Kolli Hills, India

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 2 publications
2
13
0
Order By: Relevance
“…The criteria used by farmers to describe different landraces included the seeds characteristics, agronomic and religious properties, and the growth habits of the crop. Similar results were found in other studies including on the common bean [40], fonio [41], millet [42] and Kersting's groundnut [12]. These characteristics used to identify different Kersting's groundnut landraces reflect the consistence of folk taxonomy.…”
Section: Knowledge Existence and Distribution Of Kersting's Groundnusupporting
confidence: 85%
“…The criteria used by farmers to describe different landraces included the seeds characteristics, agronomic and religious properties, and the growth habits of the crop. Similar results were found in other studies including on the common bean [40], fonio [41], millet [42] and Kersting's groundnut [12]. These characteristics used to identify different Kersting's groundnut landraces reflect the consistence of folk taxonomy.…”
Section: Knowledge Existence and Distribution Of Kersting's Groundnusupporting
confidence: 85%
“…The study of ethnobotanical research is deeply rooted within India. There are many examples of medicinal ethnobotanical surveys conducted in India in the past that have recorded many botanical remedies among many aboriginal groups: Malasars [ 26 ]; Malamalasars [ 27 ]; Malayalis [ 28 - 31 ]; Irulas [ 22 , 23 , 32 - 34 ]; Gonds [ 15 ]; Koysd, Konda reddis, Valmikis, Koyas, Chenchus, Lambadis, Jatapus, Savaras, Bagatas, Kammaras, Khondas, Nukadoras, Porjas, Jatapus [ 35 ]; Paliyar [ 36 ]; Kanikar [ 37 ]; Todas, Kotas [ 38 , 39 ]; Kattunayakas [ 40 ]; Apatani [ 41 ]; Chellipale [ 42 ]. Although there are many descriptive qualitative surveys of TAK, to our knowledge, there are no ethnobotanical studies within India that consider variation in TAK among informants using a quantitative consensus analysis.…”
Section: Introductionmentioning
confidence: 99%
“…2006c, 2007), we found a handful of studies where aboriginal informants recorded more taxa in a partuciluar area than taxonomists challenging the SK classification system (Conklin 1954; Balakrishnan et al . 2003; Rengalakshmi 2005). None of these studies allowed a direct comparison within an experimental design.…”
Section: Discussionmentioning
confidence: 99%
“…This is not the first account where TK classification systems recognize more taxa than the SK classification system. In a review of aboriginal biological classification systems (Newmaster et al 2006c(Newmaster et al , 2007, we found a handful of studies where aboriginal informants recorded more taxa in a partuciluar area than taxonomists challenging the SK classification system (Conklin 1954;Balakrishnan et al 2003;Rengalakshmi 2005). None of these studies allowed a direct comparison within an experimental design.…”
Section: Discussionmentioning
confidence: 99%